Paradoxical Cerebral Fat Embolism in Revision Hip Surgery - Piuzzi, Nicolás S. (Hindawi Publishing Corporation, 2014)
The incidence of clinical fat embolism syndrome (FES) is low (<1%) whilst fat embolism (FE) of marrow fat appears to occur more often (Mellor and Soni (2001)). Paradoxical brain FE may occur in patients undergoing hip orthopedic surgery who have an undocumented patent foramen ovale (PFO). We report a case of an eighty-year-old male patient, who underwent a scheduled revision hip surgery suffering a paradoxical cerebral FE.